Surface modification of steel runner with improved hydrophobicity for reducing the coefficient of friction for ice - Yujin Jeon; Sumit Barthwal; Jae-Kang Kim; Si-Hyung Lim (Friction)
The advancement of equipment technology is very important for winter sports competitions, but there has been a lack of research on ice friction via the modification of runner surface. In this study, we modify the surfaces of steel runners that are commonly used in winter sports to reduce ice friction by improving water repellency. A custom-built tribotester that can measure ice friction under high-speed conditions was developed. Three surface treatment processes—vapor deposition, immersion, and spraying—are applied to the steel surface to improve its hydrophobicity. The results confirm that surface treatment techniques for large areas can effectively reduce the coefficient of friction between the steel runner and ice, which is strongly related to the water contact angle of the steel runner. This highlights the effect of surface wettability on the coefficient of friction between metal surfaces and ice. The developed surface treatment methods can be applied to runner surfaces that are used in various winter sports.